Decreased elastin gene expression in noncompliant human bladder tissue: a competitive reverse transcriptase-polymerase chain reaction analysis - Djavan, B; Lin, V; Kaplan, E P; Richier, J C; Shariat, S; Marberger, M; McConnell, J D (The Journal of urology, 1998)
In low capacity noncompliant fibrotic bladders, as seen in patients with myelomeningocele, elevated storage pressures ultimately can lead to renal damage. Earlier studies have described an increased deposition of extracellular matrix protein, especially type III collagen, in the detrusor muscle. We analyzed elastin gene expression and quantified elastin gene alteration in the obstructed bladder, correlating urodynamically measured compliance with elastin messenger ribonucleic acid (mRNA) concentration. Using a reverse transcriptase-polymerase chain reaction quantitative technique elastin mRNA can be reliably measured in 5 to 8 mg. samples of bladder tissue. We compared tissue samples from patients with urodynamically demonstrated noncompliant bladders (less than 10 cc/cm. water) to a control group with normal bladder compliance (greater than 20 cc/cm. water). Tissue samples were homogenized and sonicated, and complementary deoxyribonucleic acid (cDNA) was synthetized from mRNA using reverse transcriptase. Wild type and mutant elastin cDNA were synthetized, and target elastin cDNA with unknown concentration was competitively co-amplified with known serial dilutions of the mutant template (competitive polymerase chain reaction). Computerized densitometry allowing cDNA concentration measurement was performed and competitive reverse transcriptase-polymerase chain reaction was repeated at least twice for every sample. Elastin mRNA concentration ranged from 27.6 to 63.2 attomole per mg. in noncompliant bladders compared to 62 to 190 attomole per mg. in controls. The variation within the same sample was less than 10%. There was a statistically significant difference between mean plus or minus standard deviation elastin cDNA concentration in noncompliant bladders (37.48 attomole per mg. +/- 12.06) and controls (119.63+/-41.01 attomole per mg.). A significant decrease in elastin mRNA matches the decreased deposition of elastic fibers noted in previous immunohistochemical studies. Our data suggest that this decrease is mainly due to a transcriptional down regulation of the elastin gene in noncompliant bladders.